Verification of the new trade theory in EU's trade with CEECs: Evidence from panel data 1990 - 1997 - Jarko Fidrmuc (Institute for Advanced Studies (IHS), 1999)
The new trade theory explains several features of the current development of EU's trade with CEECs better than the Heckscher-Ohlin model. In 1997, CEECs participated in the European economy with levels of intraindustry trade comparable to peripheral EU countries. However, this induced increased specialization in EU countries, which contrasts with the development in the previous decades. The development of intraindustry trade is positively related to the growth of wages and negatively to interest rates. – – Um gewisse Merkmale der gegenwärtigen Entwicklung des Osthandels der EU zu erklären, ist die neue Außenhandelstheorie besser geeignet als das Heckscher-Ohlin-Model. Im Laufe der 90er Jahre beteiligten sich die ostmitteleuropäischen Länder immer aktiver an der europäischen Arbeitsteilung. Ihre Anteile des intraindustriellen Handels entsprachen 1997 bereits jenen der peripheren EU-Länder. Dies führte zu einer verstärkten Spezialisierung innerhalb der EU, die sich deutlich von der Entwicklung der vorhergehenden Jahrzehnte unterscheidet. Der intraindustrielle Handel der EU mit den ostmitteleuropäischen Ländern hängt positiv vom Lohnwachstum und negativ von Zinssätzen ab.
Keywords: F12; F14; F15; 330; new trade theory; intraindustry trade; Kernel estimates of distribution; fixed effects model; Neue Außenhandelstheorie; intraindustrieller Handel; Kernschätzer der Verteilung; Modell mit fixen Effekten